Phitoplankton in the Western Bransfield Strait - Kuzmenko, L. V. (Ukrainian Antarctic Journal, 2004)
Species diversity, dimensional structure, abundance development and phytoplankton distribution in the waters of the western Brandsfield Strait in March 2002 were studied. Phytoplankton spatial distribution was characterized by heterogeneity, connected with the complete system of surface currents in this region. The highest indices of the phytoplankton abundance development (more than 500 mln.cells⋅m-3) were obtained for the northern part of the experimental site at the expense of nannoplankton. Biomass (up to 2117 mgּ⋅m–3) was mainly created by the large diatom algae. Shoaling water at the Antarctic Peninsular, especially in the south-western part of the experimental site was very poor for phytoplankton.